VD_FINDINFO Pron / 2013 / 283 vom 4. November 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, RADIATION DU RÔLE, FRAIS JUDICIAIRES, MESURE PROVISIONNELLE | 109 al. 1 CPC (CH), 109 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 241 CPC (CH)